Organ Augmented Reality: Audio-Graphical Augmentation of a Classical Instrument - Jacquemin, Christian; Ajaj, Rami; Le Beux, Sylvain; d’Alessandro, Christophe; Noisternig, Markus; Katz, Brian F.G; Planes, Bertrand (International journal of creative interfaces and computer graphics, 2010)
This paper discusses the Organ Augmented Reality (ORA) project, which considers an audio and visual augmentation of an historical church organ to enhance the understanding and perception of the instrument through intuitive and familiar mappings and outputs. ORA has been presented to public audiences at two immersive concerts. The visual part of the installation was based on a spectral analysis of the music. The visuals were projections of LED-bar VU-meters on the organ pipes. The audio part was an immersive periphonic sound field, created from the live capture of the organ sounds, so that the listeners had the impression of being inside the augmented instrument. The graphical architecture of the installation is based on acoustic analysis, mapping from sound levels to synchronous graphics through visual calibration, real-time multi-layer graphical composition and animation. The ORA project is a new approach to musical instrument augmentation that combines enhanced instrument legibility and enhanced artistic content.